ความรับผิดทางอาญาของนิติบุคคล : ศึกษากรณีกระทำผิดโดยประมาท - นลินอร ธิบดี (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
Nowadays, there are harms done by corporations but criminal justice process has not been very useful. This research finds that the most important factor for such failure is the lack of proper theoretical application to corporate criminal liability, particularly in the case of criminal negligent. Comparative studies of Criminal negligent for corporation in the common law countries reveal that the earlier usage of Doctrine of Identification to impose corporate criminal liability has certain limitations. The Doctrine which states that act and intention of a legal person’s representative are of those of juridical legal person was found to entail practical flaws. This research finds that the countries that concern with such harm have resorted to the process of legal reformation and introduced new measures. Especially, the common law countries where the doctrine of Identification was used to determine corporate criminal liability is now changed to the more modern ‘Aggregation theory’ and ‘Organisational Fault theory.’ Upon analysis, this research also finds that theory on corporate criminal liability in Thailand needs reform. Therefore, models for reform in some countries would be the guideline for appropriate legal changes in Thailand as well.